2017
DOI: 10.3389/fphys.2017.00739
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Markers aSMA, Krt14, and Krt19 Unveil Elements of Murine Lacrimal Gland Morphogenesis and Maturation

Abstract: As an element of the lacrimal apparatus, the lacrimal gland (LG) produces the aqueous part of the tear film, which protects the eye surface. Therefore, a defective LG can lead to serious eyesight impairment. Up to now, little is known about LG morphogenesis and subsequent maturation. In this study, we delineated elements of the cellular and molecular events involved in LG formation by using three epithelial markers, namely aSMA, Krt14, and Krt19. While aSMA marked a restricted epithelial population of the term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
6
27
0
Order By: Relevance
“…Edar was previously reported in the LG epithelial pre-bud at E14 (Pispa et al, 2003). However, LG branching morphogenesis seemed delayed and did not initiate before E16 in mice from the C57BL/6J background, compared with E15 in ICR mice (Kuony and Michon, 2017) (Fig. S1).…”
Section: The Eda Pathway Is Active In Embryonic and Adult Lg Epitheliumsupporting
confidence: 62%
See 2 more Smart Citations
“…Edar was previously reported in the LG epithelial pre-bud at E14 (Pispa et al, 2003). However, LG branching morphogenesis seemed delayed and did not initiate before E16 in mice from the C57BL/6J background, compared with E15 in ICR mice (Kuony and Michon, 2017) (Fig. S1).…”
Section: The Eda Pathway Is Active In Embryonic and Adult Lg Epitheliumsupporting
confidence: 62%
“…In our previous work, we showed an increase of epithelial ductal tree complexity and amount of terminal end buds (TEBs) during LG early branching morphogenesis, from E16 to E18 (Kuony and Michon, 2017). Here, we used the same approach to investigate the impact of Eda loss-of-function on LG ductal and acinar compartment formation at E17 and E18 ( Fig.…”
Section: Early Lg Morphogenesis Is Unaffected By Eda Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable expression of KRT15andKRT19 in oral squamous cell carcinoma (OSCC) and squamous intraepithelial neoplasm (SIN) results in their divergent biological behaviors and roles in pathogenesis, indicating that they may be used as markers to classify OSCC and SIN [33]. KRT19 may also function as a speci c epithelial marker [34]. Expression of KRT19 in the skin may be an additional characterization of skin stem cells under pathological and normal conditions [35].…”
Section: Discussionmentioning
confidence: 99%
“…1e) and Epcam (Additional file 5: Figure S2 A), while endothelial cell marker VEGFR2 or fibroblast marker FAP-α could not be detected (Additional file 5: Figure S2 A), suggesting that the spheroid cells were epithelia rather than endothelial cells or fibroblasts. Previous studies indicated that Krt14 is the marker for stem/progenitor cells of secretory glands [11][12][13]. In the adult mouse LG, the basal cells of ducts and myoepithelial cells express keratin (Krt)14, suggesting that these cells might have the characteristics of lacrimal gland stem cells (LGSCs; [14].…”
Section: Isolation and Characterization Of Lgscsmentioning
confidence: 99%